[18F]-Fluoroestradiol PET/CT: a modern look at nuclear medicine applications - A. V. Parnas; A. I. Pronin; V. S. Ilyakov; N. A. Meshcheryakova; Z. Kh. Kamolova; A. I. Mikhaylov (ABV-press, 2021)
Breast cancer is one of the most commonly diagnosed cancers and the leading cause of cancer mortality among women. Approximately 70-80 % of breast cancers are estrogen (ER) and/or progesterone receptor-positive, thus making endocrine therapy an important stage of treatment. Receptor expression in breast cancer cells is usually assessed by tissue immunohistochemistry. The method of positron emission tomography, combined with computed tomography (PET/CT), makes it possible to evaluate not only anatomical and structural, but also metabolic changes in tumor tissue. 18F-Fluoroestradiol (18F-FES) is a radiopharmaceutical drug, an estradiol analogue, which is used in the diagnostics of ER-expressing tumors and is utilized for detection and quantification of ER expression in vivo. Various studies show that 18F-FES accumulation indicates presence of ER-positive tumor tissue, which, in most cases, is confirmed by tissue immunohistochemistry. Although current guidelines recommend 18F-fluorodeoxyglucose PET/CT when routine examinations demonstrate ambiguous results, 18F-FES PET/CT can be the preferable imaging modality in the diagnostics of ER-positive breast cancer. It should be noted, that PET/CT with 18F-FES can also be effective for evaluation of tumors with a high level of ER expression, like ovarian cancer.